(untitled) (Indian Journal of Arid Horticulture, 2025)
The study was conducted to examine the solar radiation distribution in different parts of 7- year’s old guava plants and its subsequent effect on fruit quality. The interception of solar radiation was decreased markedly with the depth of plant canopy from top to bottom as well as with increase plant density. More than 3/4th of incoming radiations were intercepted by upper one meter periphery of guava plants irrespective of plant spacing. The fruit quality in terms of size, weight, TSS, vitamin C and overall palatability was significantly reduced with the depth of plant canopy and decrease in plant spacing. The upper canopy fruits particularly of widely spaced plants were better than others. Winter season fruits were double in weight and more palatable as compared to rainy season fruits.